2023
DOI: 10.1210/jendso/bvad081
|View full text |Cite
|
Sign up to set email alerts
|

Periostin in Osteoporosis and Cardiovascular Disease

Abstract: Context Osteoporosis and cardiovascular disease, prevalent disorders worldwide, often coexist and share common risk factors. The identification of common biomarkers could significantly improve patients preventive care. Objectives The objectives are 1/to review periostin involvement in osteoporosis and in cardiovascular disease and 2/identify if periostin could be a common biomarker. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…As prevalent public health issues with widespread impact and significant consequences, OP and CVD have consistently garnered considerable attention. While numerous prior epidemiological studies have reported the connection between these conditions, the precise association remains elusive (34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Several factors may contribute to this ambiguity.…”
Section: Discussionmentioning
confidence: 99%
“…As prevalent public health issues with widespread impact and significant consequences, OP and CVD have consistently garnered considerable attention. While numerous prior epidemiological studies have reported the connection between these conditions, the precise association remains elusive (34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Several factors may contribute to this ambiguity.…”
Section: Discussionmentioning
confidence: 99%